Tata Kelola Pertambangan Melalui Kebijakan Pencabutan Izin yang Berwawasan Lingkungan: Perspektif Hukum Administrasi Negara - Wahyu Nugroho (Jimly School of Law and Government, 2023)
Management of mineral and coal mining resources relies heavily on a governance system that is oriented towards good governance, and environmental and sustainable principles, as mandated by the constitution in Article 33 of the 1945 Constitution—policy for revoking mineral and stone Mining Business Permits (Indonesian: Izin Usaha Pertambangan/IUP). The President's implementation of coal is part of efforts to improve the mining and environmental governance system. The first problem is, what is the authority, mechanism, and criteria for revoking mining business permits from an administrative law perspective? secondly, does the revocation of an IUP have implications for a good mining and environmental governance system? The method used in this research is a normative juridical method, sourced from primary, secondary, and tertiary legal materials, with qualitative data analysis techniques. The first conclusion, the mechanism for revoking an IUP starts from a comprehensive evaluation of the IUP from planning to post-implementation of mineral and coal mining activities, based on administrative, technical, environmental, and financial evaluations. The criteria for IUPs that are revoked are IUPs that do not submit Work Plan and Budget reports, IUPs that do not operate, and IUPs that do not carry out post-mining reclamation obligations and do not carry out environmental management. Second, the revocation of an IUP has three implications, namely juridical, sociological, and environmental implications. The juridical implications are policies for regulating and improving the mining governance system in Indonesia as well as the government's consistency in implementing the green constitution. The sociological implication is to obtain community social support capacity and local community access to natural resource management rights. Finally, the implications of environmental insight, as a global commitment to implementing sustainable development principles, are integrated into the licensing system for mining business activities.